Polylogarithmic Connections With Euler Sums - Sofo, Anthony (Sarajevo Journal of Mathematics, 2024)
Polylogarithmic functions are intrinsically connected with sums of harmonic numbers. In this paper we explore many relations and explicitly derive closed form representations of integrals of polylogarithmic functions and the Lerch phi transcendent in terms of zeta functions and sums of alternating harmonic numbers.